Menentukan Kematangan Buah Manggis Menggunakan Metode Summary Squared Error (SSE) yang Diaplikasikan pada Belt Conveyor Pemisah Buah - Hari Risanti Saputra; Firdaus - -; Derisma - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
All parts of mangosteen are useable. In order to obtain some qulified mangosteen, it is need to make a belt conveyor sorting system which is able to sort based on it’s diameter and maturity. To obtain the maturity decision it is used Sum Squared Error (SSE) methode which find the minimum error of image RGB value between mangoosten rind color and the color templates. When need to derive the diameter, it is utilize the hough circle transform method.The results give 86% accuracy of maturity detection, 10.9% error accuracy of diameter measurements when mangosteen stalks are up and 3.4% error in diameter value when mangoosteen stalks are down .